ASPEK ESOTERIS DALAM SYI’IR ERANG-ERANG SEKAR PANJANG (SUATU EDUKASI ETIS DALAM SASTRA PESANTREN) - Abdullah, Muhammad (Faculty of Humanities, Diponegoro University, 2012)
The article uses manuscripts of Erang-erang Sekar Panjang as the object of research from two sources: one which is kept at the National Library and the other is of personal collection in Kaliwungu and Pekalongan. Those manuscripts were chosen for they contain Islamic poetry familiar to most Javanese Moslems and expressions of esoteric Sufism and Islamic moral teachings. The method used here is philological and thematic. The philological method has an aim to get text that is far from error. The thematic method, on the other hand, aims to study the main topic of the text. It is then analyzed how the Islamic poetry and hizb and wirid approach Allah through the use of basmallah, subhanallah, la ilaha illallah, hasbunallah and so on and how the Koran teaches Moslems to reflect the traits of Allah through tanzih or tasybih. By comparing the manuscripts I conclude that the first manuscript is older, and more complete. The content of doctrine escathology and theology is about the doctrine of Islamic ‘Aqidah, such as (1) the traits of Allah, (2) Quran as a qadim or jaded, (3) the human being action, (4) qada’ and qadar, (5) punishment problems, (6) heaven and hell, and so on. Keywords : syi’ir, performing-art, Islamic manuscript, esoteris, wirid.